Talc reinforcement of polylactide and biodegradable polyester blends via injection-molding and pilot-scale film extrusion - Helanto, Karoliina; Talja, Riku; Rojas, Orlando J. (Journal of Applied Polymer Science, 2021)
The authors wish to thank Arctic Biomaterials Oy for the compounding of the masterbatches, the assistance of Sai Li with the preparation of injection-molded specimens, and Laura Koskinen for the help with the figures. The research group of Paper Converting and Packaging Technology at Tampere University was gratefully acknowledged for conducting the extrusion coating trials and oxygen barrier measurements. As a renewable and biodegradable polymer, polylactide (PLA) has taken a foothold in the packaging industry. However, the thermomechanical and barrier properties of PLA-based films need to be improved to facilitate a wider adoption. To address this challenge, we examined the effect of talc reinforcement in composites based on PLA and a biodegradable polyester. Masterbatches of the polymers and talc were produced by melt compounding and processed by either injection-molding or film extrusion in a pilot-scale unit operating at 60–80 m/min. The effect of talc was investigated in relation to the morphological, thermal, mechanical, and barrier properties of the composites. Based on SEM-imaging, talc was found to increase the miscibility of PLA and the polyester while acting as a nucleating agent that improved PLA crystallinity. While this effect did not track with an increased mechanical strength, the composites with 3–4 wt% talc displayed a significantly higher barrier to water vapor. Compared to the neat polymer films, a reduction of water vapor transmission rate, by ~34–37%, was observed at 23°C/50% RH. Meanwhile, the systems loaded with 1 wt% talc showed a reduction in oxygen transmission rates, by up to 34%. Our results highlight the challenges and prospects of commercial PLA-based blends filled with talc from films extruded in pilot-scale units. Peer reviewed